The Prophetic Education Values on Surah al-’Alaq - Zumrodi, Zumrodi (ADDIN, 2021)
The Qur’an, the last book that was revealed to the Prophet Muhammad, contains instructions that regulate all aspects of human life. The Qur’an not only regulates the affairs of the hereafter or ritual worship, but the Qur’an also regulates world affairs or social worship. One of the most important matters that the Qur’an pays attention to is the issue of education. This study aims to explore the five components of prophetic in education contained in Surat al-’Alaq. This type of research is library research using descriptive qualitative methods. The analysis used is content analysis, namely by analyzing the contents of the texts which are research data. While the data sources include primary data sources and secondary data sources. The primary data sources are the interpretation of al-Munir by Wahbah az-Zuhaili and the interpretation of al-Mishbah by Quraish Shihab. While the secondary data includes various books of interpretation, journals and other books that are relevant to the research. As for the findings, that the components of education contained in the Surah al-’Alaq: First, Allah SWT as an educator. Second, Prophet Muhammad SAW as a student. Third, educational materials that are not dechotomous. Fourth, the method of education with habituation and repetition. Fifth, educational media has a very important meaning. In Surah al-’Alaq it is called “al-Qalam” or writing tools.